Respuestas
Respuesta dada por:
0
Resolver.
Aplicas productos notables.
(a + b)(a - b) = a² - b²
(√10 - √17)(√10 + √17) =
(√10)² - (√17)² =
10²/² - 17²/² =
10 - 17 =
-7
Respuesta.
- 7
Aplicas productos notables.
(a + b)(a - b) = a² - b²
(√10 - √17)(√10 + √17) =
(√10)² - (√17)² =
10²/² - 17²/² =
10 - 17 =
-7
Respuesta.
- 7
Respuesta dada por:
0
Es una DIFERENCIA DE CUADRADO ![(A+B)(A-B) = A^{2} - B^{2} (A+B)(A-B) = A^{2} - B^{2}](https://tex.z-dn.net/?f=%28A%2BB%29%28A-B%29+%3D++A%5E%7B2%7D+-+B%5E%7B2%7D+)
![( \sqrt{10} - \sqrt{17} )( \sqrt{10} + \sqrt{17} ) ( \sqrt{10} - \sqrt{17} )( \sqrt{10} + \sqrt{17} )](https://tex.z-dn.net/?f=%28+%5Csqrt%7B10%7D+-+%5Csqrt%7B17%7D+%29%28+%5Csqrt%7B10%7D+%2B+%5Csqrt%7B17%7D+%29++)
![(\sqrt{10} ) ^{2} - (\sqrt{17})^{2} (\sqrt{10} ) ^{2} - (\sqrt{17})^{2}](https://tex.z-dn.net/?f=+%28%5Csqrt%7B10%7D+%29+%5E%7B2%7D++-++%28%5Csqrt%7B17%7D%29%5E%7B2%7D++)
10 - 17
-7
10 - 17
-7
Preguntas similares
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años